Managemen Pemeliharaan dan Perawatan Mesin - - Margono (Universitas Muhammadiyah Semarang, 2006)
In the system of traditional servicing and maintening which is not planning can be happen, distruction/, failure of tools. To make a bold stand against the possibilities of efection, some of the industries has already started with planning program and it is now wellknown the system service and maintenance management.Kata Kunci : Management, Maintenance, Machine